Jogos digitais para desenvolver noções de alfabetização de crianças com transtorno do espectro autista - Coronel, Renata Cristiane Martins (2022)
The present Master's dissertation, entitled "Digital Games to Develop Literacy Notions in Children with Autistic Spectrum Disorder", is inserted in the Postgraduate Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT), in the research line School Organization, Training and Pedagogical Practices, within the research group Laboratory of Studies on Information and Communication Technologies in Education (LêTECE), and aims to understand how digital games can contribute to children with Autism Spectrum Disorder (ASD) to appropriate notions of literacy. The study was developed with the methodology of researchtraining in cyberculture, in which the production and analysis of data were carried out with three children with ASD, aged between 5 and 6 years old, in the initial literacy phase, with whom we proposed the use of three digital games that aimed to develop literacy notions with the mediation of their mothers. The data analysis was carried out based on the results of the practices with the use of digital games carried out by the children through the survey of recurring themes in the narratives of the mediating mothers that reveal literacy notions. The results indicate that digital games can contribute to the development of literacy notions, such as motor, reading, communication, listening, understanding, and creation skills, and can also contribute to the mobilization of digital literacies, such as the recognition of icons and audios, as well as the analysis and interpretation of information in the context of multiple digital languages. We conclude, through the experiences lived in this research, that, with the use of digital games, children build new cognitive skills, presenting a greater engagement, motivation, interaction and attention, which are important elements for the development of literacy notions of children with ASD, among other possible knowledge, with the social use of Digital Network Technologies.